(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the learning styles of fourth-grade students in class IV-B at SDN 07 Pontianak City. The background of this research is based on the differences in students’ learning characteristics observed during the learning process, where some students appear to understand the material more easily through visual means, while others through auditory or hands-on activities. This study employs a qualitative approach with a descriptive method. The subjects of the research are all 19 students of class IV-B. Data were collected through questionnaires and observations used to identify students’ learning style tendencies based on visual, auditory, and kinesthetic categories. The data analysis technique is conducted through stages of data reduction, data presentation, and conclusion drawing. The research results indicate that the learning styles of students in class IV-B of SDN 07 Pontianak Kota are diverse, but are dominated by the visual learning style. Based on the questionnaire, there are 9 students with a visual learning style, 3 auditory, and 7 kinesthetic. Meanwhile, the observation results show 8 students with a visual style, 7 auditory, and 4 kinesthetic. These findings indicate the importance for teachers to apply a variety of learning strategies that can adjust to students’ learning style characteristics so that the learning process is more effective and enjoyable.